GAMBARAN KASUS PERDAGANGAN ANAK DI PUSAT KAJIAN DAN PERLINDUNGAN ANAK KOTA MEDAN TAHUN 2016 - ENNI YUSRIANI (JURNAL ILMIAH KOHESI, 2018)
Trafficking in persons is a cruel crime against human rights, which ignores the right of a person to live freely, notto be tortured, personal freedom, mind and conscience, religion, the right not to be enslaved, and others.Women and children are the most victims of trafficking in persons, placing them in a very risky position thatrelates to their health, both physically and mentally, and is very vulnerable to violence, unwanted pregnancies,and sexually transmitted infections including HIV / AIDS. Such conditions of children and women will threatenthe quality of the mother of the nation and the future generation (Maidin, 2012). The National Commission forChild Protection in North Sumatra noted that 2013-2014 was the third largest case of sexual crime in the world,whose numbers were increasing. The number of cases of 52% is the practice of sexual crimes against children,physical violence, neglect, exploitation and trafficking of children (child trafficking), then forms of sexual crimesexperienced by children in North Sumatra also vary, ranging from oral sex, sodomy, sexual abuse, to rape